Hashtags of Justice: A Cultural Perspective on Indonesian Netizens use of Social Media as A Shortcut to Justice - Farah Hanifah Nuraini; Ivana Revania Effendi; Kenasty Sausan Azmi; S Sintya; Zahra Oktavia Ramadhani; Afriza Animawan Arifin (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Amidst rapid global digitalization, social media has become a new public space for Indonesians to voice injustices. When formal legal processes are often perceived as slow, unresponsive, and even biased, many citizens choose to viralize issues as an alternative strategy to drive change. This study aims to understand the perceptions, psychological, and cultural factors that motivate Indonesian citizens to viralize issues. A descriptive qualitative method was used to select informants using a purposive technique, consisting of informants who are issue-responsive Indonesian citizens. Data was collected through Focus Group Discussion (FGD) and analyzed using thematic analysis. The results show 2 main themes: (1) The perceptions of Indonesian citizens in viralize issues on social media as an effort to demand justice (2) What are the cultural and psychological factors that encourage people to participate in viralize issues on social media. These findings are supported by Tajfel & Turner's theory of social identity and Baron & Byrne's theory of conformity. Social media has become an important tool for Indonesian society to fight for justice due to distrust in the legal system as a collective strategy stemming from experiences of injustice.